Impact of the Metabolic Syndrome on Mortality is Modified by Objective Short Sleep Duration. Issue 5 (17th May 2017) - Fernandez‐Mendoza, Julio; He, Fan; LaGrotte, Caitlin; Vgontzas, Alexandros N.; Liao, Duanping; Bixler, Edward O.
Abstract : Background: To examine whether objective sleep duration is an effect modifier of the impact of metabolic syndrome (MetS) on all‐cause and cardiovascular disease/cerebrovascular mortality. Methods and Results: We addressed this question in the Penn State Adult Cohort, a random, general population sample of 1344 men and women (48.8±14.2 years) who were studied in the sleep laboratory and followed up for 16.6±4.2 years. MetS was defined by the presence of 3 or more of obesity (≥30 kg/m 2 ), elevated total cholesterol (≥200 mg/dL), triglycerides (≥150 mg/dL), fasting glucose (≥100 mg/dL), and blood pressure (≥130/85 mm Hg). Polysomnographic sleep duration was classified into clinically meaningful categories. Among the 1344 participants, 22.0% of them died during the follow‐up. We tested the interaction between MetS and polysomnographic sleep duration on mortality using Cox proportional hazard models controlling for multiple potential confounders ( P <0.05). The hazard ratios (95% CI) of all‐cause and cardiovascular disease/cerebrovascular mortality associated with MetS were 1.29 (0.89–1.87) and 1.49 (0.75–2.97) for individuals who slept ≥6 hours and 1.99 (1.53–2.59) and 2.10 (1.39–3.16) for individuals who slept <6 hours. Interestingly, this effect modification was primarily driven by the elevated blood pressure and glucose dysregulation components of MetS. Conclusions: The risk of mortality associated with MetS is increased in those with short sleep duration. Short sleep in individuals with MetS may be linked to greater central autonomic and metabolic dysfunction. Future clinical trials should examine whether lengthening sleep improves the prognosis of individuals with MetS.